PEMANFAATAN SISTEM CAD/CAM/CAE DALAM REVERSE DAN FORWARD ENGGINEERING UNTUK TURBIN FRANCIS - Djodikusumo, Indra; Santoso, Lukman; Haris, Rahmat (Mesin, 2007)
The oil price has been increasing since the last few years. Since then the utilization of hydro power plant has also been increasing. The hydro power plant is very well known as environtmental friendly power plant and therefore its utilization is demanded all around the world. Indonesia has planned to build up until 488 MW micro and mini hydro power plant until the year 2020. Half of this is micro-hydro power plant and the other half is mini-hydro power plant. The turbines for micro-hydro power plant have been produced locally, but the other half which are mini-hydro power plant are still imported from foreign countries. It is the intention of this applied research to develop the capability of local industry to design and manufacture the Francis turbine for mini-hydro power plant from 300 kW until 5 MW. The utilization of CAD/CAM/CAE System is very intensif during the development phases. Reverse and forward engineering has been applied for this purpose. The good result has been achieved. The continuous improvement shall be done in the future in order to have the better result.